Children's literature in primary schools - Waugh, David (Great Britain : Sage Publications, Incorporation, 2013)
This book made extensive use of case studies of trainee teacher work with literature in schools, to show the potential for literature to be both entertaining and informative. Readers including even most reluctant, will find here ideas for working in the classroom, as well as an introduction to texts they may never have read.
Chapter1. developing a love of reading -- Chapter2. Sharing literature with children -- Chapter3. literature across the curriculum -- Chapter4. Books for younger children -- Chapter5. Picture books -- Chapter6. Stories and poems from and about different cultures -- Chapter7. Traditional stories and fairy tales -- Chapter8. Fiction with addresses issues -- Chapter9. Fantasy and magic -- Chapter10. Classic fiction -- Chapter11. Everyday fiction -- Chapter12. Poetry .
Includes bibliographical references and index.
Keywords: CHILDRENS LITERATURE -- STUDY AND TEACHING